2020
DOI: 10.3390/ijms21041396
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Kinase Is Upregulated in Metastatic Breast Cancer Cells and Contributes to Migration and Invasion by Activation of PI 3-Kinase and Akt

Abstract: Ceramide kinase (CerK) is a lipid kinase that converts the proapoptotic ceramide to ceramide 1-phosphate, which has been proposed to have pro-malignant properties and regulate cell responses such as proliferation, migration, and inflammation. We used the parental human breast cancer cell line MDA-MB-231 and two single cell progenies derived from lung and bone metastasis upon injection of the parental cells into immuno-deficient mice. The lung and the bone metastatic cell lines showed a marked upregulation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Apart from chemoresistance, we showed that CERK promoted TNBC migration (Fig. 2 d, e), which is in line with the findings of a recent study on the contribution of CERK to migration and invasion in metastatic breast cancer cells [ 13 ]. Similar to CERK, C1P was reported to increase migration and invasion in pancreatic cancer cells [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Apart from chemoresistance, we showed that CERK promoted TNBC migration (Fig. 2 d, e), which is in line with the findings of a recent study on the contribution of CERK to migration and invasion in metastatic breast cancer cells [ 13 ]. Similar to CERK, C1P was reported to increase migration and invasion in pancreatic cancer cells [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note that the upregulation of CERK expression (tumor/normal > 2) is found only in some TNBC patients, with a significant association with chemoresistance (Table 1 ). Previous studies using cell models and publicly available microarray data show that elevated CERK expression is linked with metastatic breast cancer and increased risk of recurrence in patients with breast cancer [ 12 , 13 , 23 ]. Specifically, CERK overexpression is also associated with decreased recurrence-free survival in patients with ER-negative breast cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The imbalance in ceramide will greatly affect the physicochemical properties of cell, leading to cellular dysfunction. It has been demonstrated that ceramide metabolism is altered in numerous cancers characterized by an elevation of the Cer pro le in tumor tissue and cancer cells [7,12,13]. We speculated that the signi cant increase in the level of the Cer lipid class in LaC could have resulted from the elevated expression of the enzymes responsible for the synthesis of ceramide.…”
Section: Discussionmentioning
confidence: 98%